Effectiveness and cost-effectiveness of the Assessment of Burden of Chronic Conditions (ABCC) tool in patients with COPD, asthma, diabetes mellitus type 2 and heart failure: protocol for a pragmatic clustered quasi-experimental study - Bjorn Winkens; Esther A. Boudewijns; Danny Claessens; Manuela Joore; Lotte C.E.M. Keijsers; Onno C.P. van Schayck; Annerika H.M. Gidding-Slok (BMJ Open)
Introduction The number of people that have one or multiple condition(s) with a chronic course is rising, which consequently challenges healthcare systems. Healthcare geared to long-term care should focus on patient-centredness, shared decision making and self-management. The Assessment of Burden of Chronic Conditions (ABCC) tool was developed to integrate these elements in daily healthcare practice. The ABCC tool assesses and visualises burden of disease(s), helps to make shared decisions and stimulates self-management. The present paper documents a protocol for a quasi-experimental study investigating the effectiveness and cost-effectiveness of the ABCC tool for people with chronic obstructive pulmonary disease, asthma, type 2 diabetes mellitus and/or heart failure.Methods and analysis The study has a pragmatic clustered quasi-experimental design and will be conducted in the Netherlands. The intervention will be allocated at the level of general practice. The intervention group (18 general practices, 180 patients) will use the ABCC tool during regular consultations; the control group (18 general practices, 180 patients) will maintain usual care. Outcomes include change in quality of care (Patient Assessment of Chronic Illness Care), quality of life (EuroQol-5D-5L), capability well-being (ICEpop CAPability measure for Adults), patients’ activation (Patient Activation Measure) and costs. Follow-up time will be 18 months. Outcomes will be analysed using linear mixed models.Ethics and dissemination Ethical approval was obtained from the Medical Ethics Committee Zuyderland-Zuyd Heerlen, the Netherlands (METCZ20180131). Results will be published in peer-reviewed journals and will be presented at national and international conferences.Trial registration number ClinicalTrials.gov Registry (NCT04127383).